IMPLEMENTASI STRATEGI ERGONOMI KOGNITIF UNTUK KESEHATAN MENTAL KARYAWAN BERBASIS TIM DI PT. XYZ - Ghazali, Hartana Adiputra; Widodo, Lamto; Sukania, I Wayan (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
This study aims to identify employees’ mental workload and evaluate the effectiveness of cognitive ergonomics strategies within the team-based work system at PT. XYZ. Data collection involved the NASA-TLX method for measuring mental workload, the DASS-21 questionnaire to assess psychological conditions, and employee perceptions regarding the implementation of cognitive ergonomic strategies. Additionally, Pearson correlation analysis, Failure Mode and Effect Analysis (FMEA), and a Pareto diagram were used to support data interpretation. The results showed that most respondents experienced light to moderate mental workload, with generally positive perceptions toward the applied ergonomic strategies. Although statistical correlations among variables were not significant, data patterns and field findings suggest that cognitive ergonomics contribute to stress reduction and increased productivity. In conclusion, implementing appropriate and sustainable cognitive ergonomic strategies is essential to support mental health in a team-based work environment.